Screening of Phytophagous and Xylophagous Insects Guts Microbiota Abilities to Degrade Lignocellulose in Bioreactor - Gales, Amandine; Chatellard, Lucile; Abadie, Maider; Bonnafous, Anaïs; Auer, Lucas; Carrère, Hélène; Godon, Jean-Jacques; Hernandez-Raquet, Guillermina; Dumas, Claire (Frontiers in Microbiology, 2018)
Microbial consortia producing specific enzymatic cocktails are present in the gut of phytophagous and xylophagous insects; they are known to be the most efficient ecosystems to degrade lignocellulose. Here, the ability of these consortia to degrade ex-vivo lignocellulosic biomass in anaerobic bioreactors was characterized in term of bioprocess performances, enzymatic activities and bacterial community structure. In a preliminary screening, guts of Ergates faber (beetle), Potosia cuprea (chafer), Gromphadorrhina portentosa (cockroach), Locusta migratoria (locust), and Gryllus bimaculatus (cricket) were inoculated in anaerobic batch reactors, in presence of grounded wheat straw at neutral pH. A short duration fermentation of less than 8 days was observed and was related to a drop of pH from 7 to below 4.5, leading to an interruption of gas and metabolites production. Consistently, a maximum of 180mgeq.COD of metabolites accumulated in the medium, which was related to a low degradation of the lignocellulosic biomass, with a maximum of 5 and 2.2% observed for chafer and locust gut consortia. The initial cell-bound and extracellular enzyme activities, i.e. xylanase and β-endoglucanase, were similar to values observed in the literature. Wheat straw fermentation in bioreactors leads to an increase of cell-bounded enzyme activities, with an increase of 145% for cockroach xylanase activity. Bacterial community structures were insect dependent and mainly composed of Clostridia, Bacteroidia and Gammaproteobacteria. Improvement of lignocellulose biodegradation was realized in successive batch mode at pH 8 using the most interesting consortia, i.e. locust, cockroaches and chafer gut consortia. In these conditions, lignocellulose degradation increased significantly: 8.4, 10.5 and 21.0% of the initial COD was degraded for chafer, cockroaches and locusts, respectively in 15 days. Consistently, xylanase activity tripled for the three consortia, attesting the improvement of the process. Bacteroidia was the major bacterial class represented in the bacterial community for all consortia, followed by Clostridia and Gammaproteobacteria classes. This work demonstrates the possibility to maintain apart of insect gut biological activity ex-vivo and shows that lignocellulose biodegradation can be improved by using a biomimetic approach. These results bring new insights for the optimisation of lignocellulose degradation in bioreactors.